2017
DOI: 10.1021/acssuschemeng.7b03727
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly-p-phenylene Terephthalamide (PPTA) in Ionic Liquids

Abstract: Several ionic liquids (ILs) were tested for their suitability to synthesize the aramid polymer PPTA in an attempt to diminish the dependence on the toxic N-methylpyrrolidone (NMP) that is currently used in industry. The room-temperature IL 3-methyl-1-octylimidazolium chloride ([C8MIM][Cl]) showed the highest promise as with this medium the polycondensation reaction proceeds with a similar mechanism as it happens in the solvent mixture of NMP with CaCl2.With this IL, PPTA polymer with an inherent viscosity of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Disruption of the hydrogen bonding network within the aramid fibers, as a consequence of the IL anion, can cause fibrillation and further favor their role as compatibilizers . These chemical interactions between IL and aramid have been discussed in PPTA synthesis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the hydrogen bonding network within the aramid fibers, as a consequence of the IL anion, can cause fibrillation and further favor their role as compatibilizers . These chemical interactions between IL and aramid have been discussed in PPTA synthesis …”
Section: Introductionmentioning
confidence: 99%
“…7,8 These chemical interactions between IL and aramid have been discussed in PPTA synthesis. 10,15,16 In this context, the potential of the IL C 4 MImCl and HO 2 CC 1 MImCl (Figure 1) to compatibilize aramid pulp-HNBR composites and hybrid aramid pulp-CB-HNBR composites was investigated and the rubber-filler interaction was studied through thermal, swelling, and mechanical analyses. C 4 MImCl was chosen due to the promising results obtained with SBR-aramid composites, 7,8 while HO 2 CC 1 MImCl was used due to the possible formation of hydrogen bonds between the nitrile group in the HNBR structure and the carboxyl group of the IL.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) are known to be excellent green solvents for many types of synthetic polymers and biopolymers. [33][34][35][36][37][38][39][40][41] It has also been reported that Lewis-acidic chloroaluminate ionic liquids can be used to dissolve epoxy resins of tantalum capacitors. For these reasons, we decided to explore the use of ionic liquids for the recycling of bonded NdFeB magnets for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Wholly aromatic polyamides (aramids), such as poly ( p ‐phenyleneterephthalamide) (Kevlar) and poly ( m ‐phenyleneisophthalamide) (Nomex), have been noted for their high thermal and chemical resistance, low flammability, and excellent mechanical properties and widely used in military, transportation, and other fields as high‐performance polymeric materials . However, infusibility and limited solubility in most organic solvents are characteristic properties of para ‐aramids because of the high regularity and rigidity of polymer backbones and strong interchain interactions, which make them generally intractable or difficult to process, thus greatly restricting their widespread applications.…”
Section: Introductionmentioning
confidence: 99%
“…high-performance polymeric materials. [1][2][3][4][5][6][7] However, infusibility and limited solubility in most organic solvents are characteristic properties of para-aramids because of the high regularity and rigidity of polymer backbones and strong interchain interactions, which make them generally intractable or difficult to process, thus greatly restricting their widespread applications. In addition, the high water sorption of aramids because of the presence of amide groups, compared with other aromatic polymeric materials, has caused obvious negative effect on their electrical and dielectric performance as well as mechanical properties.…”
mentioning
confidence: 99%